2021
DOI: 10.3389/fnagi.2021.729060
|View full text |Cite
|
Sign up to set email alerts
|

Free-Living Physical Activity Measured With a Wearable Device Is Associated With Larger Hippocampus Volume and Greater Functional Connectivity in Healthy Older Adults: An Observational, Cross-Sectional Study in Northern Portugal

Abstract: Several studies using neuroimaging techniques have established a positive relationship between physical activity (PA) and brain structure and function in older populations. However, the use of subjective measures of PA and the lack of multimodal neuroimaging approaches have limited the understanding of this association. This study aims to explore the associations between PA and brain structure and function by objectively evaluating PA. Community-dwelling cognitively healthy older adults (without diagnosed cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…These factors can cause variations in the health-related biological signals. Moreover, different health conditions and different environments cause variations in the functioning and performance of the different wearables, making the comparation between studies very difficult [ 4 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Differences between the studies in terms of the aims and sample sizes (number of studies included in the original reviews) made it difficult to compare them.…”
Section: Discussionmentioning
confidence: 99%
“…These factors can cause variations in the health-related biological signals. Moreover, different health conditions and different environments cause variations in the functioning and performance of the different wearables, making the comparation between studies very difficult [ 4 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Differences between the studies in terms of the aims and sample sizes (number of studies included in the original reviews) made it difficult to compare them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study reported that hippocampal subfields including cornu ammonis 1 (CA1), CA2/3 and CA4 were significantly covaried with grey matter volume in older adults with cognitive impairment compared to the normal controls (Wang et al, 2018). Another study also found that the larger left parahippocampal gyrus and right hippocampus volumes were associated with the higher physical activity ability (Domingos et al, 2021). In our previous studies, we found a significant decrease in the volume of subcortical nuclei (composing of hippocampus, thalamus, caudate, putamen, pallor and amygdala) in the CF older adults .…”
Section: Introductionmentioning
confidence: 99%